Regional economics and policy - Armstrong, Harvey (Harvester Wheatsheaf, 1993)
A substantially revised second edition of a text which aims to explain the latest developments in regional economics and policy while adding new case material from the EC, UK and USA. It includes such topics as migration patterns, and applications of input-output models to regional planning.